When diversity helps performance: Effects of diversity on conflict and performance in workgroups. Issue 2 (8th April 2014) - Ayub, Nailah; Jehn, Karen
Abstract : Purpose: – The aim of this paper is to explore whether national diversity in the form of national variety (differences in kind, e.g. number of nationalities) has a positive effect on group processes and performance whereas national separation (differences in attitudes and beliefs; i.e. social distance and national stereotypes) has a negative effect. Design/methodology/approach: – This cross-cultural comparative study examines the moderating role of national diversity in the relationship between social attitudes on conflict and performance across two samples. Participants are presented with one of the two national variety conditions (low or high national variety) who then report on social distance, national stereotype, conflict, and performance. Findings: – National separation negatively relates to performance and positively relates to conflict. However, there is less conflict and higher performance, despite national separation, when there is high national variety. Research limitations/implications: – This study is limited to individual perceptions. Research could be extended to experienced conflict and effects of individual national separation on conflict and performance at the group level. Practical implications: – Although social distances and negative stereotypes may not be completely eliminated, the results imply that managers can modify the effects by promoting and celebrating national variety. The results show that even conflict is modified (task conflict increases while relationship and process conflict decreases) when there is national variety despite social distances and negative stereotypes. Originality/value: – This study contributes to workgroup research on diversity and conflict management by exploring social attitudes and opinions. Individual attitudes are the bases of group processes and this study attends to two of the social attitudes that need to be added to our understanding of group processes.